Analysis of Subcutaneous Anterior Transposition versus in-situ Decompression of Ulnar Nerve with Force Transducer in Cadaver Specimen - Kilinc, Bekir Eray; Celik, Haluk; Oc, Yunus; Unlu, Ruhat; Keskinoz, Elif Nedret; Yilmaz, Baris (TURKISH NEUROSURGICAL SOC, 2020)
AIM: To evaluate the changes in the pressure values of the ulnar nerve after in-situ decompression and anterior subcutaneous transposition of the ulnar nerve. MATERIAL and METHODS: The ulnar nerve was released in the postcondylar groove. An ultrathin (100 lm) force transducer was embedded between the posterior of the ulnar nerve and the anterior of the medial epicondyle. The elbow joint was flexed from full extension position to maximum flexion and was measured to obtain the maximum stress at 0 degrees, 45 degrees, 90 degrees, and 135 degrees of flexion. Then, the ulnar nerve was transposed anterior subcutaneously. The same measurement was applied to the two procedures. Data were compared between the two surgical techniques. RESULTS: Our study was performed on the right upper extremities of eight (seven men and one woman) fresh frozen cadavers. The mean age of the cadavers was 67.25 +/- 12.2 years. Mean values of 0 degrees, 45 degrees, 90 degrees, and 135 degrees of flexion after the ulnar nerve insitu decompression were 0.41, 0.9, 1.7, and 4.3 N, respectively. Mean values of 0 degrees, 45 degrees, 90 degrees, and 135 degrees of flexion after anterior transposition of the ulnar nerve were 0.3, 0.73, 1.63, and 2.15 N, respectively. No significant difference was noted between the two groups in terms of 0 degrees, 45 degrees, and 90 degrees of flexion values. However, there was a significant difference between the two groups in the 135 degrees of flexion measurement values. CONCLUSION: Anterior transposition is a more appropriate technique than in-situ decompression in the treatment of cubital tunnel syndrome that does not respond to conservative treatment regardless of the severity of the symptom.
Keywords: Entrapment neuropathy; Ulnar nerve; In-situ decompression; Anterior transposition; Flexiforce